Hemorrhagic Meningioma With Symptom of Convulsion: A Rare Presentation of Parietal Meningioma - Phuong Hoai , Dinh Thi; Thanh Van, Duong Ngoc; Tho, Phan Quoc; Anh Thu, Nguyen Ngoc; Phuoc, Le Trong; Hieu, Le Trong; Lac, Nguyen Vinh; Tuong, Vo Ba; Minh, Nguyen Thanh (International Clinical Neuroscience Journal, 2022)
Meningioma is the most common, extra-axial, non-glial intracranial tumor with an incidence of 2.3-5.5/100 000, accounting for 20%-30% of all primary brain tumor diagnoses in adults. Meningiomas associated with intratumoral hemorrhage are very rare occurring in 0.5%-2.4%. of individuals. Herein, we report a rare case of hemorrhagic meningioma with the symptom of convulsion. The case was a 68-year-old woman admitted to the hospital with severe headache and convulsions. Computed tomography revealed an increase in heterogeneous lesion measuring 4 × 3 × 2.5 cm at the right parietal lobe. Brain magnetic resonance imaging (MRI) showed a grossly stable homogeneously enhancing extra-axial mass measuring 43 × 33 × 28 mm, small calcified peripheral, intratumoral hemorrhage. Histopathology showed a multi-celled meningioma with bleeding areas (WHO grade I).